2017
DOI: 10.1159/000475715
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Melanoma Patients Treated with BRAF/MEK-Directed Therapy or Immune Checkpoint Inhibition Stratified by Clinical Trial versus Standard of Care

Abstract: Objectives: Since 2011, metastatic melanoma treatment has evolved with commercial approval of BRAF- and MEK-targeted therapy and CTLA-4- and PD-1-blocking antibodies (immune checkpoint inhibitors, ICI). While novel therapies have demonstrated improved prognosis in clinical trials, few studies have examined the evolution of prognosis and toxicity of these drugs among an unselected population. We assess whether survival and toxicity reported in trials, which typically exclude most patients with brain metastases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Identification and review of research literature We identified nine eligible studies that included twelve comparisons of trial and non-trial patients: Arrieta et al [28], Bertelli et al [29], De Placido et al [30], Field et al [31], Goldman et al [32], Khera et al [33], Led Du et al [34], Svensson et al [35] and Templeton et al [36]. Figure 2 contains a PRISMA flow diagram showing the selection of studies.…”
Section: Strategies For Dealing With Dilemmasmentioning
confidence: 99%
See 4 more Smart Citations
“…Identification and review of research literature We identified nine eligible studies that included twelve comparisons of trial and non-trial patients: Arrieta et al [28], Bertelli et al [29], De Placido et al [30], Field et al [31], Goldman et al [32], Khera et al [33], Led Du et al [34], Svensson et al [35] and Templeton et al [36]. Figure 2 contains a PRISMA flow diagram showing the selection of studies.…”
Section: Strategies For Dealing With Dilemmasmentioning
confidence: 99%
“…Characteristics of the studies All nine studies included comparisons concerning overall survival [28][29][30][31][32][33][34][35][36], some also included progression-free survival [29,30,32,34]. Eight of the nine studies were retrospective cohort The Kaplan-Meier analyse showed a trial effect (p = 0.007), but the univariate Cox proportional hazard ratio did not (p = 0.089) studies.…”
Section: Strategies For Dealing With Dilemmasmentioning
confidence: 99%
See 3 more Smart Citations